Cutting-edge muscle recovery - Li, Y.; Fu, F. H.; Huard, J. (The Physician and Sportsmedicine, 2005)
Muscle injuries, the most frequent type of sports-related injury, present challenging problems in traumatology and sports medicine. Injured skeletal muscle can repair itself via spontaneous regeneration, but extracellular matrix overgrowth and collagen deposition can lead to fibrosis, resulting in incomplete functional recovery and a propensity for injury recurrence. Physicians may be able to improve skeletal muscle healing after injury when researchers understand more about the mechanisms involved in scar-tissue development. Techniques may be refined to prevent muscle fibrosis - specifically via the inactivation of transforming growth factor-beta-1 - and, ultimately, improve muscle healing after injuries.